Identifying the characteristics of effective teacher professional development: a critical review - Sims, Sam; Fletcher-Wood, Harry (School effectiveness and school improvement, 2021)
Several influential reviews and two meta-reviews have converged on the position that teacher professional development (PD) is more effective when it is sustained, collaborative, subject specific, draws on external expertise, has buy-in from teachers, and is practice based. This consensus view has now been incorporated in government policy and official guidance in several countries. This paper reassesses the evidence underpinning the consensus, arguing that the reviews on which it is based have important methodological weaknesses, in that they employ inappropriate inclusion criteria and depend on an invalid inference method. The consensus view is therefore likely to be inaccurate. It is argued that researchers would make more progress identifying characteristics of effective professional development by looking for alignment between evidence from basic research on human skill acquisition and features of rigorously evaluated PD interventions.